Pola Komunikasi Organisasi dalam Meningkatkan Kinerja Karyawan di Diskominfotik Kabupaten Blitar - Khansa Mahardika Mulyono; Yefi Dyan Nofa Harumike; Nik Haryanti (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2024)
Effective communication is communication that can produce a change in attitude in each individual which is visible in a communication. This research uses a qualitative approach, with data collection techniques carried out using three techniques which include interviews, documentation, and observation or security. The research was carried out by going directly to the Blitar Regency Communication, Informatics and Statistics Service which is located on Jalan Sudanco Supriyadi Number 17, Bendogerit, Sananwetan District, Blitar City, East Java. The results of this research are based on a series of analysis processes from interview data, observation and documentation, showing that effective organizational communication patterns are very important in improving employee performance at the Blitar Regency Diskominotics. By implementing clear and transparent vertical communication, both from top to bottom and from bottom to top. Meanwhile, supporting and inhibiting factors, organizational communication patterns have a significant impact on improving employee performance. Supporting factors such as continuous training, positive work environment, constructive feedback.